Il supporto informativo alla valutazione dei rischi ed alla individuazione delle misure preventive nelle piccole e micro imprese: le schede di rischio professionale / Informatics support for risk assessment and identification of preventive measures in small and microenterprises: occupational hazard datasheets - De Merich, D.; Forte, G. (La Medicina del Lavoro, 2011)
Summary «Informatics support for risk assessment and identification of preventive measures in small and micro-enterprises: occupational hazard datasheets». Background: Risk assessment is the fundamental process of an enterprise’s prevention system and is the principal mandatory provision contained in the Health and Safety Law (Legislative Decree 81/2008) amended by Legislative Decree 106/2009. In order to properly comply with this obligation also in small-sized enterprises, the appropriate regulatory bodies should provide the enterprises with standardized tools and methods for identifying, assessing and managing risks. Objectives: To assist in particular small and micro-enterprises (SMEs) with risk assessment, by providing a flexible tool that can also be standardized in the form of a datasheet, that can be updated with more detailed information on the various work contexts in Italy. Methods: Official efforts to provide Italian SMEs with information may initially make use of the findings of research conducted by ISPESL over the past 20 years, thanks in part to cooperation with other institutions (Regions, INAIL-National Insurance Institute for Occupational Accidents and Diseases), which have led to the creation of an information system on prevention consisting of numerous databases, both statistical and documental (“National System of Surveillance on fatal and serious accidents”, “National System of Surveillance on work-related diseases”, “Sector hazard profiles” database, “Solutions and Best Practices” database, “Technical Guidelines” database, “Training packages for prevention professionals in enterprises” database). With regard to evaluation criteria applicable within the enterprise, the possibility of combining traditional and uniform areas of assessment (by sector or by risk factor) with assessments by job/occupation has become possible thanks to the cooperation agreement made in 2009 by ISPESL, the ILO (International Labour Organisation) of Geneva and IIOSH (Israel Institute for Occupational Health and Hygiene) regarding the creation of an international Database (HDODB) based on risk datasheets per occupation. The project sets out to assist in particular small and micro-enterprises with risk assessment, providing a flexible and standardized tool in the form of a datasheet, that can be updated with more detailed information on the various work contexts in Italy. Results: The model proposed by ISPESL selected the ILO’s “Hazard Datasheet on Occupation” as an initial information tool to steer efforts to assess and manage hazards in small and micro-enterprises. In addition to being an internationally validated tool, the occupation datasheet has a very simple structure that is very effective in communicating and updating information in relation to the local context. Conclusions: According to the logic based on the providing support to enterprises by means of a collaborative network among institutions, local supervisory services and social partners, standardised hazard assessment procedures should be, irrespective of any legal obligations, the preferred tools of an “updatable information system” capable of providing support for the need to improve the process of assessing and managing hazards in enterprises.